Structural and optical properties of PbS and PbS/MnTe core/shell quantum dots - Halim, Nur Diyana (2021)
The optical properties of colloidal quantum dots (QDs) are affected by the size of QDs, material used and the capping agents. This thesis explores on the study of PbS/MnTe core/shell QDs where PbS acts as the core and MnTe is the shell. The QDs had been synthesized at ambient temperature by using aqueous synthesis approach. The PbS/MnTe core/shell QDs with different shell thickness (0.3, 0.6 and 0.9 monolayer (ML)) were effectively fabricated in this study. The structural and optical characteristics of PbS QDs and PbS/MnTe core/shell QDs are also studied in this study. High-Resolution Transmission Electron Microscopy (HRTEM) and Energy Dispersive X-ray Microscopy (EDX) have been used to investigate the structural characteristics of QDs sample. According to HRTEM analysis, the average size of the PbS QDs was 4.46 ± 0.82 nm, with a spherical form. The average size of PbS/MnTe core shell QDs was increased to 4.80 ± 0.73 nm for PbS/MnTe 0.3 ML, 5.16 ± 0.80 nm for PbS/MnTe 0.6 ML and 5.53 ± 0.84 nm for PbS/MnTe 0.9 ML, respectively. The size core/shell QDs was enhanced because of the growth of MnTe shell on PbS core. Aside from that, the analysis of EDX has been performed on the samples of PbS and PbS/MnTe core/shell QDs to prove the existence of MnTe elements. The peak in EDX spectrum related with Mn and Te was identified at 5.9 keV and 3.7 keV. Photoluminescence (PL) spectroscopy was used to explore the optical characteristics and behaviour of charge carriers within PbS and PbS/MnTe QDs at various temperatures (10-300 K). The PL peak energies of PbS/MnTe core shell QDs at room temperature were blue-shifted as the shell thickness increased due to the strong confinement effect caused by presence of MnTe shell. The effect of temperature on the PL peak energy, full width half maximum (FWHM), and PL intensity can be observed in the temperature dependent PL. In general, the PL peak energy and FWHM increase monotonically as temperature increased, owing to the interaction of charge carriers with phonons. In contrast, as the temperature increased, the PL peak intensities decreased, which was related with the excitation of carriers out of the QDs into non-radiative recombination centres. The research and production PbS/MnTe core/shell QDs would be valuable in the coming decades particularly in the application of photovoltaic devices.